193k views
5 votes
Let g ( x ) = x cos ⁡ ( x ) g(x)=xcos(x)g, left parenthesis, x, right parenthesis, equals, x, cosine, left parenthesis, x, right parenthesis. Find g ′ ( x ) g ′ (x)g, prime, left parenthesis, x, right parenthesis

User Src
by
5.1k points

1 Answer

3 votes

Answer:


g'(x)=cos (x)-xsin(x)

Explanation:

If g(x)=x cos (x)

We want to determine the derivative of g(x).

Using Product rule:
{\left( {u\,v} \right)^\prime } = u'\,v + u\,v'


u=x : u'=1\\v=cos (x): v'=-sin(x)

Therefore:


g'(x)=cos (x)+x(-sin(x))\\g'(x)=cos (x)-xsin(x)

User Dominic Gurto
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.